2017
DOI: 10.3389/fchem.2017.00028
|View full text |Cite
|
Sign up to set email alerts
|

Non-fused Phospholes as Fluorescent Probes for Imaging of Lipid Droplets in Living Cells

Abstract: Molecular tools for fluorescent imaging of specific compartments in cells are essential for understanding the function and activity of cells. Here, we report the synthesis of a series of pyridyl- and thienyl-substituted phospholes and the evaluation of these dyes for fluorescent imaging of cells. The thienyl-substituted phospholes proved to be successful for staining of cultured normal and malignant cells due to their fluorescent properties and low toxicity. Co-staining experiments demonstrated that these prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…A series of non-fused pyridyl and thienyl-substituted phospholes was proposed as alternative green LD stains (Phos, as shown in Figure 4 ) [ 41 ]. It was shown that the introduction of thienyl groups to the phosphole caused shifts to the red region both in excitation and emission spectra compared to pyridyl groups.…”
Section: Recent Developments In Lds’ Selective Fluorescent Probesmentioning
confidence: 99%
“…A series of non-fused pyridyl and thienyl-substituted phospholes was proposed as alternative green LD stains (Phos, as shown in Figure 4 ) [ 41 ]. It was shown that the introduction of thienyl groups to the phosphole caused shifts to the red region both in excitation and emission spectra compared to pyridyl groups.…”
Section: Recent Developments In Lds’ Selective Fluorescent Probesmentioning
confidence: 99%
“…Great efforts have been made to develop novel lipid droplets dyes to solve these problems. [12][13][14][15][16][17][18][19][20][21] Because the normal concentration used for lipid droplets staining falls in the range of 5-10 μM or even higher, these dyes show weak emission due to the aggregation-caused quenching (ACQ) effect. 22 Few dyes have been synthesized for lipid droplets imaging and function at nano-molar concentrations.…”
mentioning
confidence: 99%
“…Donor-acceptor fluorophores, able to promote internal charge transfer (ICT), have been applied in FRET and in super-resolution STED microscopy [65][66][67]. In addition, new dyes such as pyridyl-and thienyl-substituted phospholes, fluorescent fluoranthenes, and solvatochromic coumarins were developed in recent years for LD imaging in living cells and in human cervical cancer tissues [68][69][70].…”
Section: Imaging Strategiesmentioning
confidence: 99%